Preparation of Rice Straw Cellulose Xanthate and Study on Its Adsorption Properties of Cadmium(II) from Aqueous Solutions - Pan1, Qingshan; Liu1, Wei; Ma2, Meigui; Yan1, Heping; Zhou1, Bo; Shi1, Ling; Xu1, Shijuan (Asian Journal of Chemistry, 2014)
Rice straw cellulose xanthate was prepared by modified with carbon disulphide after mercerized by sodium hydroxide solution. The modification parameters (carbon disulphide dose, hydroxide solution concentration, treatment temperature) were studied and optimized in this study. The effects of pH, adsorbent dose and contact time on the removal of Cd(II) ion from aqueous solution was studied. The results suggested that when the initial Cd(II) ion concentration was 20 mg/L, the adsorption capacity of rice straw cellulose xanthate was high effective with the rice straw cellulose xanthate dose was 5.0 g/L and the contact time was 2 h, the equilibrium adsorption capacity of rice straw cellulose xanthate was 3.86 mg/g and the removal rate of Cd(II)ion was 96.41 %. The regeneration capacities of rice straw cellulose xanthate adsorbent was investigated also in this study, the results suggested that the removal rate of Cd(II) ion was more than 76 % after several times of regeneration. All the results suggested that the rice straw cellulose xanthate can be used as a low cost but effective adsorbent for heavy metals removal form aqueous solution.